2023
DOI: 10.1158/1055-9965.epi-23-0208
|View full text |Cite
|
Sign up to set email alerts
|

Association between Outdoor Light at Night and Prostate Cancer in the Health Professionals Follow-up Study

Abstract: Background: Circadian disruption is a potential risk factor for advanced prostate cancer, and light at night (LAN) exposure may disrupt circadian rhythms. We evaluated whether outdoor LAN increases the risk of prostate cancer. Methods: We prospectively followed 49,148 participants in the Health Professionals Follow-up Study from 1986 through 2016. We estimated baseline and cumulative time-varying outdoor LAN with ~1 km2 resolution using data from the US Defense Meteorological Satellite Program’s Operational Li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, several studies have suggested no statistically significant association between ALAN exposure and prostate cancer. Chowdhury-Paulino et al reported no association between the interquartile range increase in cumulative light exposure at night and total and fatal prostate cancer incidence [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have suggested no statistically significant association between ALAN exposure and prostate cancer. Chowdhury-Paulino et al reported no association between the interquartile range increase in cumulative light exposure at night and total and fatal prostate cancer incidence [ 49 ].…”
Section: Discussionmentioning
confidence: 99%